Job creation in business services: innovation, demand, polarisation - Francesco Bogliacino; Matteo Lucchese; Mario Pianta (European Commission, Joint Research Centre (JRC), 2011)
The patterns and mechanisms of job creation in business services are investigated in this article by considering the role of innovation, demand, wages and the composition of employment by professional groups. A model is developed and an empirical test is carried out with parallel analyses on a group of selected business services, on other services and on manufacturing sectors, considering six major European countries over the period 1996-2007. Within technological activities, a distinction is made between those supporting either technological competitiveness, or cost competitiveness. Demand variables allow identifying the special role of intermediate demand. Job creation in business services appears to be driven by efforts to expand technological competitiveness and by the fast growing intermediate demand coming from other industries; conversely, process innovation leads to job losses and wage growth has a negative effect that is lower than in other industries. Business services show an increasingly polarised employment structure.
Keywords: J20; J23; O30; O33; 330; Business Services; Innovation; Employment.